Perlindungan Hukum Terhadap Investor Di Sektor Pariwisata - Rahmad Ihza Mahendra Mahendra (Fakultas Hukum, Universitas Palangka Raya, 2023)
Increasing investment in the tourism sector is one of the government's focuses, considering that the tourism sector has charm and is also supported by the geographical conditions of Indonesia, which has extraordinary natural resources that can attract tourists to visit Indonesia. To increase the interest of tourists in dating, facilities need forgiving, and building and increasing this requires significant capital from foreign and domestic investors. This study uses normative research methods to analyze the legal aspects of investment in the tourism sector and the legal protection of investors in the tourism sector. The study's results found that it was regulated in Law Number 25 of 2007 concerning Investment. However, it must synergize with the principles in Article 5 of Law Number 10 of 2009 concerning tourism and the principles of implementing investment activities in the tourism business sector subject to the General Agreement on Trade in Services (GATS) provisions. The legal protection of investors in the tourism sector is similar to legal protection for other investors with preventive legal protection.